Joint production and sustainability investment decisions for a risk-averse manufacturer under a Cap-and-trade policy - Hongling Lu; Qingguo Bai; Fanwen Meng (Sustainable Operations and Computers)
This study considers a risk-averse manufacturer that invests in sustainability technology to reduce carbon emissions under a cap-and-trade policy. In this study, stochastic demand is initially modeled as a linear function of both the sales price and sustainability level. Employing the newsvendor model framework, the objective of the risk-averse manufacturer is assessed using a mean-variance approach. By analyzing serval optimal properties of the joint operational decisions, this study provides the closed-form solutions of the sales price and sustainability level. This study further provides several numerical examples to illustrate the theoretical results and investigates the impacts of the major parameter on the operations of the risk-averse manufacturer.